The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/15228932.2010.489861
|View full text |Cite
|
Sign up to set email alerts
|

Angry Inmates Are Violent Inmates: A Poisson Regression Approach to Youthful Offenders

Abstract: The importation model of inmate behavior posits that pre-confinement characteristics and behaviors contribute to inmate misconduct; however most of this research has centered on criminal history and not psychosocial characteristics that might predict misconduct, namely anger. Controlling for 14 confounds, including psychiatric symptoms, age, race, gender, commitment offense type, and four measures of prior delinquency, anger significantly predicted sexual misconduct, staff assaults, and aggressive misconduct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 80 publications
(90 reference statements)
1
17
0
1
Order By: Relevance
“…These differences are discussed in the following. On the one hand, minors who commit crimes against persons present more individual risk factors, as it was hypothesised, such as physical aggressiveness, outbursts of anger, and insensitivity towards others, all of which are factors that have been related with psychopathic traits in juvenile delinquents or aspects of personality (Aguilar & Godoy, 2013;Barudy, 2000;Contreras et al, 2011;DeLisi et al, 2010;Herrero, 2002;Vilariño et al, 2013). On the other hand, in crimes against property, the minors that were studied were characterised by presenting a greater degree of inconsistent parenting, a factor that has also been related to delinquency in earlier studies (Kelly et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…These differences are discussed in the following. On the one hand, minors who commit crimes against persons present more individual risk factors, as it was hypothesised, such as physical aggressiveness, outbursts of anger, and insensitivity towards others, all of which are factors that have been related with psychopathic traits in juvenile delinquents or aspects of personality (Aguilar & Godoy, 2013;Barudy, 2000;Contreras et al, 2011;DeLisi et al, 2010;Herrero, 2002;Vilariño et al, 2013). On the other hand, in crimes against property, the minors that were studied were characterised by presenting a greater degree of inconsistent parenting, a factor that has also been related to delinquency in earlier studies (Kelly et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…For example, a study of traumatic experiences and misconduct among more than 800 wards in the California Youth Authority indicated that youth with greater histories of trauma engaged in more sexual misconduct, engaged in more suicidal activity, and totaled more misconduct that was reviewed by the parole board (DeLisi, Drury, Kosloski, Caudill, Conis, et al, 2010). Other studies have shown that anger/hostility/negative emotionality (DeLisi, Caudill, Trulson, Marquart, Vaughn, & Beaver, 2010) are important for understanding which juvenile inmates engage in violence while in confinement. In other words, we recognize that a host of individuallevel risk factors are associated with noncompliance and institutional violence during confinement and therefore institutional policies that rely solely on measures of psychopathy to assess risk of misconduct will be ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Tradicionalmente, el estudio de la conducta infractora en menores se centra en el abordaje de los factores de riesgo y los factores de protección, no prestando demasiada atención a variables criminológicas, como aquellas relacionadas con las tipologías de delitos y su relación con perfiles específicos de infractores (Cuervo et al, 2015). Históricamente, los delitos contra las personas se asocian a factores de riesgo de carácter personal, como la falta de empatía, la falta de control de la ira, la insensibilidad o, en general, los rasgos asociados a la órbita de la psicopatía (Aguilar y Godoy, 2013;Barudy, 2000;Contreras et al, 2011;DeLisi et al, 2010;Vilariño et al, 2013), mientras que los delitos contra la propiedad se asocian a variables sociodemográficas y a etiología ambiental como estilos educativos inconsistentes (Kelly, Macy y Mears, 2005).…”
Section: Abstract: Risk Assessment Juvenile Justice Violence Antisociunclassified